Band alignment and photovoltaic effect of epitaxial α-PbO thin films. (17th June 2015) - Majima, Eishi; Kozuka, Yusuke; Uchida, Masaki; Nakamura, Masao; Kawasaki, Masashi
Abstract: To explore a p-type semiconductor lattice-matched with perovskite transition-metal oxides, we have grown α-PbO(001) thin films on (Nb-doped) SrTiO3 (001) and GdScO3 (110) substrates by pulsed laser deposition. The photovoltaic effect in a Au/α-PbO/Nb:SrTiO3 heterojunction is enhanced compared with that in a Au/Nb:SrTiO3 Schottky junction. The band alignment is deduced from photocurrent action spectra. We conclude that α-PbO facilitates the separation of electron–hole pairs generated at the interface of the SrTiO3 side in the ultraviolet light region and of the α-PbO side in the visible light region. Our results indicate that α-PbO is a promising candidate for photovoltaic heterojunctions involving strongly correlated oxides.